Managing and Prioritising Public Finances and Budget in Support of Strategic Development in the Slovak Republic: A Targeted Budget Review - Jansen, Juliane (OECD Publishing, 2020)
This review looks at how the budgeting and public financial management system, as managed and co-ordinated by the Ministry of Finance, effectively supports Principles 2 and 3 of the OECD Recommendation on Budgetary Governance (2015). This report is divided into four sections providing recommendations at the end of each based on the OECD Principles of Budgetary Governance
Keywords: Finance and Investment; Governance; Economics; Slovak Republic; United States